Supramolecular Loading of DNA Hydrogels with Dye–Drug Conjugates for Real‐Time Photoacoustic Monitoring of Chemotherapy. Issue 1 (20th November 2022) - Borum, Raina M.; Moore, Colman; Mantri, Yash; Xu, Ming; Jokerst, Jesse V.
Abstract: A longstanding problem with conventional cancer therapy is the nonspecific distribution of chemotherapeutics. Monitoring drug release in vivo via noninvasive bioimaging can thus have value, but it is difficult to distinguish loaded from released drug in live tissue. Here, this work describes an injectable supramolecular hydrogel that allows slow and trackable release of doxorubicin (Dox) via photoacoustic (PA) tomography. Dox is covalently linked with photoacoustic methylene blue (MB) to monitor Dox before, during, and after release from the hydrogel carrier. The conjugate (MB‐Dox) possesses an IC50 of 161.4 × 10 −9 m against human ovarian carcinoma (SKOV3) cells and loads into a DNA‐clad hydrogel with 91.3% loading efficiency due to MB‐Dox's inherent intramolecular affinity to DNA. The hydrogel is biodegradable by nuclease digestion, which causes gradual release of MB‐Dox. This release rate is tunable based on the wt% of the hydrogel. This hydrogel maintains distinct PA contrast on the order of days when injected in vivo and demonstrates activatable PA spectral shifts during hydrogel degradation. The released and loaded payload can be imaged relative to live tissue via PA and ultrasound signal being overlaid in real‐time. The hydrogel slowed the rate of the murine intraperitoneal tumor growth 72.2% more than free Dox. Abstract : This report introduces a multifunctional hydrogel that allows (1) real‐time surveillance of drug release via photoacoustic tomography overlaid with ultrasound and (2) slow and local delivery of chemotherapy from gradual hydrogel degradation. The hydrogel is composed of cross‐linked DNA strands that serve as the scaffold. Doxorubicin (Dox) is covalently tagged with methylene blue (MB) for photoacoustic imaging (PAI) contrast.